Two-photon absorption cross-section investigation of visible-light photoinitiators under Q-switched Nd:YAG nanosecond pulse laser at 1064 nm - Romphosri S. (2023)
Two-photon polymerization (TPP) technologies commonly rely on femtosecond lasers such as Ti:sapphire which limits their accessibility due to high costs and complexities. Recently, multiple reports showed TPP under near-infrared irradiation which enables the use of alternative light sources such as Neodymium-doped lasers known to be affordable and efficient for a nanosecond and picosecond pulsed generation. 4,4′-Bis(dimethyl-amino) benzophenone or Michler’s ketone (MK), one of the photoinitiators commonly used for photopolymerization under UV irradiation, also shows an absorption band in the visible region which allows for two-photon polymerization at the fundamental wavelength of Neodymium-doped lasers at 1064 nm. In this report, we investigated the two-photon absorption (TPA) of MK in contrast with Irgacure-784 and Indane-1,3-dione, reported to also be promising photoinitiators for the same TPP process. Among them, MK showed a large TPA cross-section measured via the nonlinear transmission method and Z-scan technique with Q-switched Nd:YAG nanosecond pulse laser at 1064 nm, demonstrating MK as a promising photoinitiator for the low-cost two-photon polymerization.